Prevalence and Outcome of Neonates presenting with Hypoxic Ischemic Encephalopathy - Shafa; Aisha Tuz Zohrah; Riaz, Wajeeha; Eemaan, Farrah; Shaikh, Salma (Indus Journal of Bioscience Research, 2025)
Objective: To determine the prevalence and outcome of neonates presenting with hypoxic ischemic encephalopathy. Study Design: Observational descriptive study Setting: Department of Pediatrics, Neonatal care unit, Bilawal Medical College for Boys, LUMHS, Jamshoro. Duration: April 15, 2025 to July 15, 2025. Methodology: A total of 65 term newborns (delivered at ≥37completed weeks of gestation) with Hypoxic Ischemic Encephalopathy of either gender, birth weight > 2000 g were included. Newborn with Hypoxic ischemic encephalopathy was labelled as positive if she/he had low APGAR scores (< 7 at 5 min), intrapartum asphyxia (PH